1999
DOI: 10.2166/wst.1999.0597
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Evaluation of Advanced Reclaimed Water for Potable Applications

Abstract: The City of Tampa in the Southwest portion of Florida is examining the development of an advanced treatment facility for supplementing their potable water supply with highly treated reclaimed water. Full-scale microbiological monitoring of a similar treatment train demonstrated that the high-pH chemical treatment process was an effective barrier for removal and inactivation of viruses (99.99%), bacteria (99.9999%) and enteric protozoa (99.9%). A constructed pilot plant and bench-scale studies of the high-pH ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2001
2001

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It was found that microorganism reductions were a result of physical removal and that protozoa remained viable. Therefore, the high pH did not affect the viability of the protozoa as it did the viruses (Rose et al, 1999).…”
Section: Comparison Of the Final Reclaimed Water Quality With The Recmentioning
confidence: 95%
“…It was found that microorganism reductions were a result of physical removal and that protozoa remained viable. Therefore, the high pH did not affect the viability of the protozoa as it did the viruses (Rose et al, 1999).…”
Section: Comparison Of the Final Reclaimed Water Quality With The Recmentioning
confidence: 95%
“…Under experimental conditions all three disinfectants met the WHO microbial guidelines. Tampa, Florida investigated the use of highly treated reclaimed water for potable applications (Rose et al, 1999). Removal and inactivation of viruses (99.99%), bacteria (99.9999%) and enteric protozoa (99.9%) were achieved.…”
Section: Wastewater Reusementioning
confidence: 99%